Atom probe tomography applied to the analysis of irradiated microstructures. Issue 9 (27th January 2015) - Marquis, Emmanuelle A.
Abstract: Abstract : With its particular ability to image solute clusters in three dimensions and impurity segregation to selected interfaces and grain boundaries, atom probe tomography has provided unique insight into the effects of irradiation on materials microstructures. This article reviews the contribution of atom probe tomography to our understanding of behaviors and responses of structural materials under irradiation. Possible atom probe tomography based approaches and common data analysis methods to analyze the microstructural features often observed in irradiated materials are described. In particular, the analysis of solute clustering, solute segregation, and void imaging are discussed in the context of radiation-induced hardening of austenitic steels and reactor pressure vessel steels, and the development of oxide dispersion strengthened steels, radiation-induced solute segregation to grain boundaries for stress corrosion cracking or corrosion issues, and to understand the swelling response of irradiated materials. While highlighting the unique information that atom probe tomography can offer, common limitations, current challenges, and outstanding technical questions regarding data analysis and interpretation are also presented.